The simulated consumer – an agent-based approach to shopping behaviour - Rauh, Jürgen; Schenk, Tilman A.; Schrödl, Daniel (ERDKUNDE, 2012)
Recent research on consumption has indicated a growing differentiation of consumption styles and habits, which in turn make the shoppers’ decisions increasingly hard to grasp and more complex in general. In particular, it is found that the classic modelling techniques fail to sufficiently represent these decision processes. This paper examines the potentials of an agent-based approach for the locational choices of consumers for their shopping activities on a regional level. The model is applied to two product sectors, groceries and clothing, in two distinct research areas in northern Sweden and southern Germany. While the empirical findings generated for the two case studies resulted in quite different model designs, both are found to be equally applicable for representing the different choice mechanisms and result in forecasts of buying power flows and thus turnovers of individual shops. It is concluded that agent-based approaches provide an elaborate instrument to model consumer locational choices and to forecast consequences of planning decisions, although expanding the empirical basis on qualitative grounds of research may lead to still further advancements.